THE ROLE AND DYNAMICS OF SURKHANDARYA DISTRICTS IN TERRITORIAL DEVELOPMENT PROCESSES - Qosimova Nodira Saidovna (Modern American Journals, 2025)
This article analyzed the role of the districts of the Surkhandarya region in territorial development processes, their socio-economic development dynamics, and interregional disparities. The study examined indicators of economic activity, production potential, agricultural and service sector development, infrastructure conditions, and employment levels at the district level. Based on statistical data, the development rates of the territories were compared, and leading as well as lagging districts were identified. Additionally, the main factors influencing territorial development and the existing challenges were revealed.
Keywords: Territorial development, Surkhandarya region, districts, socio-economic dynamics, interregional disparities, economic potential, infrastructure, employment, sustainable development